Amphibian community structure in Isau-Isau Wildlife Reserve, South Sumatra, Indonesia - RHAMDHON DOROJATUN TANJUNG; MIRZA DIKARI KUSRINI; ANI MARDIASTUTI; INDRA YUSTIAN; ARUM SETIAWAN; MUHAMMAD IQBAL (Society for Indonesian Biodiversity, 2023)
Abstract. Tanjung RD, Kusrini MD, Mardiastuti A, Yustian I, Setiawan A, Iqbal M. 2023. Amphibian community structure in Isau-Isau Wildlife Reserve, South Sumatra, Indonesia. Biodiversitas 24: 6836-6843. Amphibian community structures in Isau-Isau Wildlife Reserve, South Sumatra, were investigated from Mei until July 2023. The data were obtained by Visual Encounter Survey combination with line transect. The data analyzed were Species Richness (Margalef Index), Diversity Index (H', Shannon-Wiener), Dominance (D, Simpson Index), and Evenness Index (J', Pielou) calculated using PAST 4.0 software. In addition, we also analyzed abiotic factors such as air temperature, humidity, water temperature, pH, total dissolved solids (TDS), and dissolved oxygen (DO). The abiotic data were included as explanatory variables in Canonical Correspondence Analysis (CCA). A total of 12 amphibian species consisting of 11 genera and 4 families were recorded. Of them, 11 species are classified as least concern, while one species, Theloderma licin, is classified as data deficient by the IUCN Red List of Threatened Species.